2017
DOI: 10.1155/2017/2149156
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors for Low Birth Weight among Term Newborns in Adwa General Hospital, Northern Ethiopia

Abstract: Background. World health organization estimates that 25 million LBW babies are born annually worldwide and 95% occur in developing countries. Objective. To assess the prevalence and associated factors of low birth weight among term neonates delivered in Adwa Hospital, Northern Ethiopia. Methods. A cross-sectional study was conducted among neonates delivered in Adwa Hospital. All live births delivered from July 1, 2014, to June 30, 2016, were included in this study. The study participants were selected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
71
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 12 publications
14
71
8
3
Order By: Relevance
“…The finding of this study indicated that 19.53%, of neonates were born with low birth weight. The finding of this study is higher than the studies done in Northern Ethiopia (10%) (Gebregzabiherher, Haftu, Weldemariam, & Gebrehiwet, 2017), Axum and Laelay Maichew district (9.9%) (Teklehaimanot, Hailu, & Assefa, 2014), Kenya (12.3%) (Muchemi, Echoka, & Makokha, 2015), Northeast Nigeria16.9%, (Takai, Bukar, & Audu, 2014), Jakarta Indonesia (4. 5%) (Yanita, 2010), Nepal11.7% (Singh, Shrestha, & Marahatta, 2010), Iran (6.8%) (Jafari, Eftekhar, Pourreza, & Mousavi, 2010) and Abha City Saudi Arabia18.8%, (Baijayanti, Faten, & HAM, 2012).Whereas it is lower than studies done in Kersa, West Ethiopia (28.3 %) (Assefa, Berhane, & Worku, 2012) and Gambia (22.5%) (Jammeh, Sundby, & Vangen, 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…The finding of this study indicated that 19.53%, of neonates were born with low birth weight. The finding of this study is higher than the studies done in Northern Ethiopia (10%) (Gebregzabiherher, Haftu, Weldemariam, & Gebrehiwet, 2017), Axum and Laelay Maichew district (9.9%) (Teklehaimanot, Hailu, & Assefa, 2014), Kenya (12.3%) (Muchemi, Echoka, & Makokha, 2015), Northeast Nigeria16.9%, (Takai, Bukar, & Audu, 2014), Jakarta Indonesia (4. 5%) (Yanita, 2010), Nepal11.7% (Singh, Shrestha, & Marahatta, 2010), Iran (6.8%) (Jafari, Eftekhar, Pourreza, & Mousavi, 2010) and Abha City Saudi Arabia18.8%, (Baijayanti, Faten, & HAM, 2012).Whereas it is lower than studies done in Kersa, West Ethiopia (28.3 %) (Assefa, Berhane, & Worku, 2012) and Gambia (22.5%) (Jammeh, Sundby, & Vangen, 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…Socioeconomic factors associated with low birth weight include place of residence, occupation, educational status, and wealth index [9]. Similarly, maternal factors associated with low birth weight include preterm delivery, history of low birth weight, maternal age, height, Hb level, iron supplementation, and frequency of Ante Natal Care (ANC) visit [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal birth weight (NBW) babies, LBW is the single most important factor of neonatal and infant mortality, especially of deaths within the 30 days of life . LBW has been associated with not only poorer health and development in children but also with adverse health outcomes in later life such as mental retardation, learning disability, ischemic heart disease and chronic hypertension etc …”
Section: Introductionmentioning
confidence: 99%